HPV status in unknown primary head and neck cancer: Prognosis and treatment outcomes. (27th August 2018) - Cheraghlou, Shayan; Torabi, Sina J.; Husain, Zain A.; Otremba, Michael D.; Osborn, Heather A.; Mehra, Saral; Yarbrough, Wendell G.; Burtness, Barbara A.; Judson, Benjamin L.
Abstract : Objectives: Approximately 3% to 9% of head and neck cancer presents with a metastatic node and no identifiable primary tumor. These cases of head and neck carcinoma of unknown primary (HNCUP) present a therapeutic challenge. Therapy of this disease varies based on factors such as institutional, surgeon, and patient preference. Evidence demonstrating the outcomes associated with these therapies for HNCUP is limited, and among the available series, the tumor human papillomavirus (HPV) status is often ignored. Treatment deintensification has been proposed for a subset of these patients. We aim to evaluate the treatment‐related outcomes for HPV‐associated and HPV‐negative HNCUP. Methods: A retrospective study of 978 adult HNCUP diagnosed from 2010 to 2013 in the NCDB was conducted. Multivariate Cox survival regressions as well as univariate Kaplan‐Meier analyses were conducted. Results: Patients with HPV‐associated disease had superior survival, with a 3‐year survival of 94.8% (standard error [SE]: 1.0), compared with 80.3% (SE: 2.9) among those with HPV‐negative disease. Among HPV‐negative patients with clinical nodal classification (cN)2/cN3 disease, treatment with definitive radiotherapy alone compared to definitive chemoradiotherapy was associated with diminished survival (hazard ratio 5.507, P  = 0.005). Among patients with HPV‐associated cancer and cN2/cN3 disease, all treatments (surgery alone, surgery with adjuvant radiotherapy, surgery with adjuvant chemoradiotherapy, definitive chemoradiotherapy, definitive radiotherapy) resulted in statistically equivalent survival. Conclusion: Tumor HPV status has a significant prognostic value for HNCUP and should be considered in future studies of treatment deintensification in this group. Treatment deintensification to radiotherapy alone in cN2/cN3 cases may result in poorer patient survival for HPV‐negative patients, whereas it may be a promising option for further investigation in HPV‐positive patients. Level of Evidence: 4 Laryngoscope, 129:684–691, 2019